Corporate Governance Review, Carbon Emission Disclosure and Corporate Value: A Study on Energy Sector Companies Listed on the Indonesia Stock Exchange - Yolifiandri, Yolifiandri; Kamil, Islamiah; Anjarwati, Sri; Royani Damayanti, Ida; Parashakti, RD (Dinasti International Journal of Economics, Finance & Accounting, 2024)
Protecting the natural environment is a very important responsibility for all people and organizations. The natural environment includes all the natural elements that make up the Earth's living system, including air, water, soil, and all living things that live in it. It has an important role, because it provides the necessary resources for humans and other living things. If we do not pay attention to the environment, then Nature will be damaged and the environment around us will become polluted, of course it can be detrimental to human life and also have the impact of damage in the future. One of the major contributors to environmental damage is from industry. Therefore, the author tries to provide proposals that are expected to be solutions to prevent environmental damage to the business world and also as a form of participation in environmental concern and is expected to increase the value of the Company. The author will explain the problems related to how to increase the value of the Company which has been with the image of the Company can only take advantage of nature without taking into account the damage caused. The author not only discusses how to increase the value of the Company, but also discusses how to have good corporate governance by paying attention to the surrounding environment, namely by discussing carbon emission disclosure. The author uses the social documentation analysis method which is expected to find theories and examine factors that can raise the Company while still paying attention to the environment by conducting research on companies from industries listed on the Indonesia Stock Exchange. This research is useful as a result of the implementation of good governance and the disclosure of carbon emissions as a further mitigation of natural damage.